Pharmacodynamic effects and kinetic disposition of rabeprazole in relation to CYP2C19 genotype in healthy Chinese subjects - HU Yong-mei; XU Jian-ming; MEI Qiao; XU Xin-hua; XU Shu-yun (Acta Pharmacologica Sinica; Vol 26, No 3 (March 2005): Acta Pharmacologica Sinica, 2016)
Aim: To investigate whether the pharmacodynamics and pharmacokinetics of rabeprazole are dependent on CYP2C19 genotype status in healthy Chinese Han subjects. Methods: The CYP2C19 genotype status of healthy Chinese Han volunteers was determined using the polymerase chain reaction-restriction fragment length polymorphism method. Twenty healthy subjects volunteered to participate in the study. There were seven homozygous extensive metabolizers (homEM), six heterozygous extensive metabolizers (hetEM), and seven poor metabolizers (PM). All subjects were Helicobactor pylori-negative, which was determined by serology and 13C-urea breath tests. Rabeprazole (20 mg) was taken orally once daily in the morning for 8 days, and intragastric pH values were monitored for 24 h by Digitrapper pH after day 1 (single dose) and day 8 (repeated dose). Meanwhile, blood samples were collected at various time-points for 24 h after administration. The serum concentrations of rabeprazole were measured using high-performance liquid chromatography. Results: The mean area under the curve (AUC) values for rabeprazole differed among the three different genotype groups, with a relative ratio of 1.0, 1.3, and 1.8 after a single dose and 1.0, 1.1, and 1.7 after repeated doses in the homEM, hetEM, and PM groups, respectively. Mean AUC values for rabeprazole after a single dose and after repeated doses were significantly different between the homEM and PM groups, but not between the homEM and hetEM or hetEM and PM groups. No significant differences in intragastric pH median, pH>4 total time, and pH>4 time percentage of 24 h, were observed among the three different genotype groups after a single dose or after repeated doses of rabeprazole. Conclusion: In healthy Chinese Han subjects, the pharmacokinetics of rabeprazole are dependent on a certain degree on CYP2C19 genotype status; however, the acid-inhibitory efficacy of rabeprazole is not influenced significantly by CYP2C19 genetic polymorphism.